Efektivitas Media Vascak Physics Animation untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Rangkaian Listrik Dc - Noer Fitri; Zakirman Zakirman (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this study is to improve students' understanding of concepts on DC electrical circuit material by using Vascak Physic Animation media. This type of research is quasi-experimentation with before after design. The subjects of this study were 32 students of class XII MIPA 1 SMA Widya Nusantara Kota Bekasi for the 2023-2024 academic year, consisting of 13 students and 19 students. The research data collection instrument uses a description test prepared based on five indicators of understanding concepts. Data analysis using paired sample t-test based on pretest and posttest data shows that there is a significant difference between before using Vascak Physics Animation and after using Vascak Physics Animation and the results of the Gain (N-Gain) test of 78% so that it is concluded that there is an influence of the use of online media vascak physics animation on students' understanding of concepts and the use of physics learning media Vascak Physics Animation shows effective improve students' understanding of concepts on DC electrical circuit material in class XII MIPA 1 SMA Widya Nusantara Bekasi City.